Investigating In-service Teachers’ Beliefs and Self-efficacy about Mathematical Modelling Using a Structural Model of Professional Competence for Teaching Mathematical Modelling - Khoza, Siyabonga Jabulane (University of the Witwatersrand, Johannesburg, 2023)
In this study, I investigate in-service teachers’ beliefs and self-efficacy about teaching mathematical modelling. I further understood teachers’ perceptions about teaching modelling in the Grades 10 - 12 CAPS mathematics curriculum. The purpose of the study was to reveal teachers’ beliefs and SEF to support the development of teachers' modelling competency. The study was underpinned by a structural model of professional competence for teaching mathematical modelling among in-service teachers. A structured questionnaire with a 5 Likert scale was used to collect data on the ISTs' beliefs, SEF, and prior knowledge about teaching modelling in the Grade 10 – 12 CAPS curriculum. Further semi-structured interview sessions were secured with three participants to further confirm quantitative data. Thus, a ‘Sequential explanatory research design from a mixed method research design’ was used to report the collected data. From the questionnaire obtained results, three major themes were formulated from the research questions and used to analyse, present, and discuss the data, which were ISTs’ beliefs about mathematical modelling, ISTs’ self-efficacy about mathematical modelling, and ISTs’ prior knowledge about modelling. From the qualitative data, four themes stood out from the data during the transcription process, namely, teachers are more product-driven than process, learners should take the lead during mathematical modelling, the curriculum timeframe limits learners from exploring modelling, and the limitation of mathematics content in the curriculum. What was revealed from the data is that teachers do believe in the existence of modelling in the mathematics curriculum. Teachers showed being constructivists in the classroom when teaching mathematics in general, including modelling. Their prior experiences with teaching modelling showed that it has contributed to their belief in teaching and learning modelling. Though teachers' beliefs and prior knowledge in this study showed to be developed and acquired respectively, to sufficiently show competencies of teaching modelling in the classroom. However, their SEF to diagnose learners' abilities during their modelling processes showed to be limited. Meaning, teachers did not show confidence in their abilities to diagnose learners' abilities when modelling, and it was not confirmed if they can identify learners' abilities when solving mathematical tasks in general. I believe in South African modelling can be taught and learnt in the classroom if it is sufficiently catered for in the curriculum and if teachers get the necessary support in teaching modelling. The value of the study is an important contribution to teachers' mathematical modelling competency.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Education (Mathematics) by Research, to the Faculty of Humanities, Wits School of Education, University of the Witwatersrand, Johannesburg, 2023.
Keywords: Beliefs; Mathematical modelling; Prior knowledge; Self-efficacy; In-service teachers; UCTD; SDG-4: Quality education